2020
DOI: 10.1093/inthealth/ihaa087
|View full text |Cite
|
Sign up to set email alerts
|

Progress in the elimination of lymphatic filariasis in the Western Pacific Region: successes and challenges

Abstract: The Western Pacific Region is the largest and most diverse region in the world, made up of 37 countries and territories in the Pacific, Oceania and parts of Asia, with a population of more than 1.9 billion people stretching over an area from China and Mongolia in the north to New Zealand in the south. In 1999, 22 countries and territories in the Pacific joined together and launched the Pacific Programme to Eliminate Lymphatic Filariasis. Shortly after, the Global Programme to Eliminate Lymphatic Filariasis was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…[18] So, eradication of this disease, which is endemic in over 50 countries, is crucial. [6,18,29,33–41] In this systematic review and meta‐analysis, we assessed the efficacy and safety of IDA in microfilariae filtration and so on the elimination of LF.…”
Section: Discussionmentioning
confidence: 99%
“…[18] So, eradication of this disease, which is endemic in over 50 countries, is crucial. [6,18,29,33–41] In this systematic review and meta‐analysis, we assessed the efficacy and safety of IDA in microfilariae filtration and so on the elimination of LF.…”
Section: Discussionmentioning
confidence: 99%
“…6 As a result, in recent years, the above mentioned countries have all failed a transmission assessment survey (TAS) or pre-TAS-either countrywide, in specific implementation units, or in some hotspots within endemic implementation units. 5,7 A series of studies has also demonstrated persistent transmission of LF in some of these countries, and research partners have provided continuous feedback to relevant health ministries/departments to emphasize the critical importance of intensifying and sustaining LF interventions to relevant health ministries/departments. [8][9][10][11][12][13][14][15][16] All these factors combined have made the development of a new strategy to accelerate LF elimination crucial.…”
Section: Lymphatic Filariasis Situation In the Pacific Before The Int...mentioning
confidence: 99%
“…Annual rounds of MDA have continued throughout the Pacific, and by the year 2020, 8 of 16 LF-endemic countries and territories (50%)—namely, Kiribati, Niue, Palau, Republic of the Marshall Islands, the Cook Islands, Tonga, Wallis and Futuna, and Vanuatu—had achieved elimination of LF as a public health problem and received validation of that status by the WHO. 5 …”
Section: Introductionmentioning
confidence: 99%
“…The Global Programme to Eliminate Lymphatic Filariasis (GPELF) has conducted an intensive mass drug administration (MDA) programme since 2000 to interrupt transmission of LF [3], and the burden of infection is estimated to have been reduced dramatically to 50 to 70 million infections in 2018 [1,2]. By 2020, 7.7 billion MDA treatments had been delivered and 17 countries or territories (eight of which are in the Pacific region [4]) have been validated as having eliminated LF as a public health problem [3,5].…”
Section: Introductionmentioning
confidence: 99%